2023
DOI: 10.1126/sciadv.adg8687
|View full text |Cite
|
Sign up to set email alerts
|

The phenotype and genotype of fermentative prokaryotes

Timothy J. Hackmann,
Bo Zhang

Abstract: Fermentation is a type of metabolism pervasive in oxygen-deprived environments. Despite its importance, we know little about the range and traits of organisms that carry out this metabolism. Our study addresses this gap with a comprehensive analysis of the phenotype and genotype of fermentative prokaryotes. We assembled a dataset with phenotypic records of 8350 organisms plus 4355 genomes and 13.6 million genes. Our analysis reveals fermentation is both widespread (in ~30% of prokaryotes) and complex (forming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 141 publications
0
12
0
Order By: Relevance
“…The simple definition of fermentation could be broadened to address some of these cases. It has been suggested the definition be broadened to include protons as an electron acceptor and H 2 as a second electron donor (Hackmann and Zhang 2023 ) (Table 1 ). The definition could likewise be broadened to include CO 2 as an electron acceptor.…”
Section: What Is Fermentation?mentioning
confidence: 99%
See 3 more Smart Citations
“…The simple definition of fermentation could be broadened to address some of these cases. It has been suggested the definition be broadened to include protons as an electron acceptor and H 2 as a second electron donor (Hackmann and Zhang 2023 ) (Table 1 ). The definition could likewise be broadened to include CO 2 as an electron acceptor.…”
Section: What Is Fermentation?mentioning
confidence: 99%
“…2 ). These studies examined descriptions of 8 300 prokaryotes, using both Bergey's Manual and the primary literature, and they found over 1/4 of these organisms carry out fermentation (Hackmann and Zhang 2021 , 2023 ). The definition of fermentation used in these studies is shown in Table 1 .…”
Section: Fermentative Organisms Are Diversementioning
confidence: 99%
See 2 more Smart Citations
“…Aerobes, however, are different from anaerobes, and these differencesthough subtleare legible in their genomes. Aerobes tend to have larger genomes (4) with more O 2 utilizing enzymes (2,5) and usually belong to specific phylogenetic groups (4). Conversely, anaerobes make use of diverse fermentation pathways to conserve energy in low O 2 settings (3, 5).…”
Section: Introductionmentioning
confidence: 99%